Can Organic Agriculture Feed the Smallholders? Experience from Rural Bangladesh. Issue 1 (June 2021) - Sarker, M. A.; Hoque, M.; Chowdhury, A. H.; Ferdous, Z.
This study empirically tests the benefit of the smallholders from organic farming in Bangladesh through their improved food security which is realised from their increased productivity and farm income. The respondent smallholders were picked up from two districts of Bangladesh namely Mymensingh and Bogra. The respondents (80) were the beneficiaries of the organic agriculture promotion project of Bangladesh Agricultural University. Three years data were collected by the project staff and were crosschecked with the base line. Findings of the study explored that before joining with the project extreme majority (93%) of the small farmers were involved in rice mono-culture and more than half (67%) of them were food deficit. The study also revealed that at the initial year of joining organic agriculture project their farm productivity was 10–12% lesser and it increased continually in the successive years. In some cases, it crossed the yield compared to conventional farming. The findings of the study showed that 100% of the farmers have followed crop diversification with high value vegetables and spices along with rice. Due to adoption of organic practices, the cost of production of the smallholders has declined from 27% to 36% and additionally they enjoy 10% to 15% premium prices which have enhanced their farm income significantly. The study shows that 62.5% of the smallholder farmers had attained household food security due to adoption of organic agriculture. Thus, adoption of organic agriculture effectively increased smallholders' access to surplus safe food. However, the study also explored that farm size, extension media contact, access to assured market and access to institutional support are the most important factors in improving smallholders' household food security through participation in organic agriculture programme. Thus, it can be concluded that organic agriculture can feed the smallholders in a better way.